The Effectiveness of the Application of Diversion by the Drug Investigation Unit of the Sleman Police in Handling the Crime of Drug Abuse Against Minors - Rezky Iria Borneo (Advances in Police Science Research Journal, 2021)
Drugs among the community today is a very prominent problem, the development of today's times, especially in the line of information and technology brings an influence that greatly impacts the occurrence of criminal abuse of narcotics, illegal drugs, and other addictive substances or drugs among the community. Problems occur when drugs are misused to cause a variety of problems, especially for minors. In the handling of drug abuse crimes, normative handling remains through the applicable legal channels, but in the case of its handling in minors must be diversion efforts as regulated in Law no.11 of 2012 on the Criminal Justice System of Children. The preparation of this thesis uses a qualitative approach with the type of field research. Then to discuss the problem of the ineffectiveness of the prosecution of this psychotropic crime, the researcher uses the theory of effectiveness and concepts related to the focus of the problem in this research. The results of this study can be concluded that the implementation of diversion implementation is still fairly less effective although the results obtained can be seen from the report 3 (three) years earlier, the repetition of drug abuse crimes is not done but, cases of drug abuse crimes with new people are still occurring, meaning that the implementation of this diversion is still not maximal and effective, the need for skilled police members in handling cases of drug abuse by children and the need for socialization related to diversion to the community so as not to cause negative stigma related to diversion in similar cases. Diversion has a lot of positive impact compared to the negative impact, but back again to its effectiveness that is not maximal if not evaluated and maximum supporting factors.